KAJIAN KETERLINDIAN LOGAM BERAT DARI LIMBAH SLAG BAJA UNTUK PEMANFAAATAN LANGSUNG TANPA MELALUI SOLIDIFIKASI - Mustika Wulandari, Rafida
The large amount of steel slag generated encourages iron and steel industry to conduct the waste utilization. In Indonesia, steel slag is classified into hazardous waste. This led the slag utilization should refer to Ministry of Environment Regulation No.02/2008 which requires the form of utilization comply with the technical requirements and be safe for the environment. One of steel slag’s direct utilization in the civil and geotechnical field is to use it as materials without solidification for embankment construction. Steel slag contains heavy metals as one of the main sources of pollution. The absence of solidification process allows high mobility of heavy metals which are released from steel slag into the environment. This research analyzes the steel slag’s characteristics and heavy metal leachability before it is utilizied as embankment construction materials. The characteristic analysis includes physical and chemical characteristics. The heavy metals leachability analysis was conducted using standard TCLP test, multiple-TCLP test, and dynamic leaching test with rainwater simulation. This study uses four samples of electric arc furnace slag with different particle size of each sample. Various characteristics of steel slag may affect the heavy metals leachability. Steel slag contains Ba, Cd, Cr, and Hg as the main heavy metals that must be considered which concentration are 501 - 555.5 mg/kg, 9.25 - 16.25 mg/kg, 814 - 1711 mg/kg, and 4.25 - 8.25 mg/kg, respectively. Standard TCLP test indicates steel slag has no toxicity characteristic based on the heavy metals concentrations in the formed leachate. The percentage of Ba, Cd, Cr, and Hg concentrations that leached through the three stages of multiple-TCLP test are 6.58 - 45.33 %, 3.11 - 17.96 %, 0.01 - 8.26 %, and 7.52 - 20.31 %, respectively. Generally, the heavy metals concentrations decrease in every stage multiple- TCLP test. Percentage of Ba, Cd, Cr, and Hg concentrations that were leached after six days of dynamic leaching test also amounts to 1.99 - 8.91 %, 4.29 - 13.12 %, 0.28 - 0.48 %, and 4.89 - 16.91 %, respectively. The small concentration of heavy metals leached indicates high stability of these metals in the steel slag. Visually, the patterns of the four metals concentrations leached during six days of dynamic leaching test generally tend to follow the logaritmic regression equation. The heavy metals concentrations leached through the standard TCLP test, multiple-TCLP test, and dynamic leaching test are comply with the TCLP quality standard by PP 19/1999 jo. PP 85/1999.